(untitled) (Nueva Epoca, 2025)
This article aims to review the political and institutional context of the past forty years in Argentina, marked by the restoration of constitutional democracy. This process entailed both a re-signification of democracy and a reconfiguration of law. Since 1983, it is no coincidence that all legislation — particularly the new Civil and Commercial Code (CCCN) — has been enacted under the ideological influence of the constitutional paradigm, with guiding principles and rules designed to guarantee human rights and protect human dignity. The paper invites a reflection on the importance of remembering where we come from, as a means to better understand what we have achieved.